Change Mantra in Nigeria: The Promises and Expectations - Okolo, Philips O; Karimo, Tari Moses (EBSU Journal of Social Sciences and Humanities, 2021)
This paper assessed the change mantra in Nigeria. The change mantra is not an entirely new lexicon in the Nigerian political lexicography but became pronounced after the emergence of the All Progressives Congress (APC) as a political party in 2014. Change was defined to mean a movement from an original state of affairs to a new and or different state, indicating that change could be positive or negative. Po sitive change is transformational in nature and content causing an upward movement from a state of disrepair, abandonment and generally undesirable to one of repair and generally more desirable. The All Progressives Congress was defined to mean an amalgam of strange bird fellows. The man President Muhammadu Buhari has served in various capacities as an Officer in the Nigerian Army and until now was seen as a no-nonsense man. Upon his emergence as the President of the Federal Republic of Nigeria, expectations were high based on the change he and his party promised. Thus this paper appraised the change mantra in Nigeria, juxtaposing it with the experience of Tanzania under President Mugulifi. The conclusion drawn is that, except in the fight against terrorism, the change government in Nigeria under Buhari has not performed too well, but that there is room for improvement given that the government is just about two years.